Analysis of the force in the process of opening and closing the door - Saelillah, Mannanu Minni (Maliki Interdisciplinary Journal, 2024)
In the process of opening and closing the door, several forces occur, including drag and pushing force. Force itself means pull or push. In addition to the force in this process occurs also the moment of force (torque) that occurs on the door hinge during the process of opening and closing the door. closing the door. This article is the result of a study of force analysis in the process of opening and closing doors. closing the door. The analysis shows that the ease or difficulty of opening and closing the door depends on the distance between the door hinges and the and closing the door depends on the distance between the door hinge and the door handle.